A influência dos fenômenos meteorológicos de escala sinótica na escala micrometeorológica - Cardoso, Nélia Kainara Rodrigues (2013)
In this paper we present a study on the influence of synoptic scale weather phenomena on the scale micrometeorological, to the town of Cruz Alta – RS. For this we used the precipitation data, satellite images for the years 2009 and 2010. Through the technique of quantile were obtained with the days on which heavy precipitation were considered those with values above or equal to 0,85 quantile. After determining the days of heavy precipitation, an analysis of satellite imagery was used to identify which weather phenomenon caused such events. The objective of this study is to analyze the influence of these events on synoptic scale micrometeorological, through the behavior of some micrometeorological variables before, during and after the passage of meteorological phenomena. As well as studying the spectral of turbulent energy in order to evaluate the turbulent field associated with episodes of extreme precipitation. From the results it appears that there is a strong influence of synoptic scale phenomena on the scale micrometeorological. It can also be concluded that besides the strong influence these phenomena caused micrometeorological variables in the behavior of some of these variables had a type of behavior depending on the phenomenon in question.